VD_FINDINFO Décision / 2013 / 407 vom 27. Januar 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 393 al. 1 let. c CPP (CH)